Hemodynamic Assessment via Echocardiography During Propofol Anesthetic Induction in Healthy Dogs - Cabral de Oliveira, Thais [UNESP]; Andraus Bispo, Guilherme [UNESP]; Beatriz de Socorro Poleto, Laura [UNESP]; Dantas de Maio Martinez, Francisco [UNESP]; Túlio Rocha de Souza, Max [UNESP]; Calazans Menescal Linhares, Lais [UNESP]; Onghero Tafarel, Marilda; Luís Ferreira, Wagner [UNESP]; Sérgio Patto dos Santos, Paulo [UNESP] (Wiley, 2024)
Introduction: Propofol is an intravenous anesthetic administered as a bolus or continuous infusion during anesthetic induction and maintenance. Its pharmacokinetic characteristics include hepatic and extrahepatic metabolism with a rapid onset of action and short duration, which provides a smooth anesthetic induction without excitatory efects. Objective: To evaluate whether the isolated use of propofol in anesthetic induction in dogs changes the hemodynamic variables assessed via echocardiography. Study Design: Prospective clinical study. Animals: Twelve healthy dogs. Methods: Te dogs were induced with propofol (dose/efect) at 3 mg/kg/minute, and echocardiographic evaluations were performed immediately before anesthetic induction (MB) and immediately after its interruption (MI), at the end of the supply of the anesthetic agent. Results: A signifcant reduction was observed between the values of the following hemodynamic variables: Ejection Fraction (EF %), which varied from 70% to 65% (p = 0.011) between moments, and the Doppler Ejection Index (DEI), which ranged from 27.1 mL/beat/m2 to 22.4 mL/beat/m2 (p = 0.044). Te heart rate (HR) and the other studied hemodynamic variables showed no signifcant diferences between the evaluated moments. Conclusion and Clinical Relevance: Propofol was a safe anesthetic-inducing agent, maintaining stable hemodynamic indices during anesthetic induction at the used rate.
Keywords: heart rate; hemodynamics; myocardial function; stroke volume; TIVA